2023
DOI: 10.3390/ph16010103
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Reduces Neoplastic Progression in Cervical Cancer Cells by Downregulating the Cyclooxygenase 2 Pathway

Abstract: Cervical cancer is the fourth-most common type of cancer in the world that causes death in women. It is mainly caused by persistent infection by human papillomavirus (HPV) that triggers a chronic inflammatory process. Therefore, the use of anti-inflammatory drugs is a potential treatment option. The effects of piperine, an amino alkaloid derived from Piper nigrum, are poorly understood in cervical cancer inflammation, making it a target of research. This work aimed to investigate the antitumor effect of piperi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…In this respect, the secretion of the cytokines studied, IL-8, IL-1β and IFN-γ, and the expression of MAPKs (ERK and p38) were reduced following treatment with piperine, thus indicating a further mediating effect of this compound on HEp-2 and SCC-25 cells. Thus, our data corroborates other results from our research group, in which a decrease in cytokine levels (IL-8, IL-1β) and ERK and p38 was also observed in HeLa, SiHa and CaSki cervical cancer cells after treatment with piperine [35]. Other studies also mention this action of piperine in decreasing ERK and p38 in breast cancer cells [39]; in addition, Western blot results confirmed that piperine decreased the expression of JNK and p38 in human ovarian cancer cells [40].…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, the secretion of the cytokines studied, IL-8, IL-1β and IFN-γ, and the expression of MAPKs (ERK and p38) were reduced following treatment with piperine, thus indicating a further mediating effect of this compound on HEp-2 and SCC-25 cells. Thus, our data corroborates other results from our research group, in which a decrease in cytokine levels (IL-8, IL-1β) and ERK and p38 was also observed in HeLa, SiHa and CaSki cervical cancer cells after treatment with piperine [35]. Other studies also mention this action of piperine in decreasing ERK and p38 in breast cancer cells [39]; in addition, Western blot results confirmed that piperine decreased the expression of JNK and p38 in human ovarian cancer cells [40].…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, the secretion of the cytokines studied IL-8, IL-1β, IF-γ, and the expression of MAPKs (ERK and p38) were reduced following treatment with piperine, thus indicating a further mediating effect of this compound on HEp-2 and SCC-25 cells. Thus, our data corroborates other results from our research group, in which a decrease in cytokine levels (IL-8, IL-1β) and ERK and p38 was also observed in HeLa, SiHa and CaSki cervical cancer cells after treatment with piperine [26]. Other studies also mention this action of piperine in decreasing the phosphorylation of ERK and p38 in breast cancer cells [27], in addition, Western blot results confirmed that piperine decreased the phosphorylation of JNK and p38 in human ovarian cancer cells [28].…”
Section: Discussionsupporting
confidence: 92%
“…The results also show that P2 displays higher cytotoxic activity, with a lower IC50 value and with a statistically significant reduction in cell viability, starting from a concentration of 12.5 µg/mL ( Figure 8 B). Other studies have also demonstrated that piperine causes a concentration-dependent reduction in cell viability of rectal [ 61 ], cervical [ 62 ], and prostate cancer cells [ 63 ]. However, the IC50 of piperine in these studies lies around 30 µg/mL, showing that piperine is even more active in metastatic gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studied effects of piperine, both in vitro and in vivo, are included the induction of apoptosis [ 72 , 73 ], the inhibition of cell proliferation [ 63 , 74 ] with cell cycle arrest [ 70 , 73 ], and the modulation of the expression of genes and proteins involved in the processes of cell migration and invasion [ 75 , 76 ]. All these effects influence the outcome of carcinogenesis of various types of tumors, such as breast [ 77 , 78 ], cervical [ 62 , 79 ], and colorectal [ 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%